Increasing Quality of Life and Reducing HIV Burden: The PATH+ Intervention - Blank, Michael B.; Hennessy, Michael; Eisenberg, Marlene M. (AIDS and behavior, 2014)
The heightened risk of persons with serious mental illness (SMI) to contract and transmit human immunodeficiency virus (HIV) is a public health problem. Our objective was test the effectiveness of a community-based advanced practice nurse intervention to promote adherence to HIV and psychiatric treatment regimens call Preventing AIDS Through Health for Positives (PATH+). We enrolled 238 HIV-positive subjects with SMI who were in treatment at community HIV provider agencies from 2004 to 2009. Participants in the intervention group were assigned an advanced practice nurse who provided community-based care management at a minimum of one visit/week and coordinated their medical and mental healthcare for 12 months. A parallel process latent growth curve model using three data points for biomarkers (baseline, 12 and 24 months) and five data points for health related quality of life (baseline, 3, 6, 12, and 24 months) showed moderate to excellent fit for modeling changes in CD4, viral load, and mental and physical SF-12 subscales. Results suggest that positive effects for PATH+ persisted at 24 months; 12 months after the intervention ended. This project demonstrates the effectiveness of a nurse-led, community-based, individually tailored adherence intervention. We demonstrated improved outcomes in individuals with HIV/SMI and regarding health-related quality of life and reductions in disease burden.